Cognitive Response Styles and the Construction of Personal Narratives: Implications for Psychopathology in Young Adults. (March 2018) - Banks, Megan V.; Salmon, Karen
We investigated the concurrent relationships among life story variables (autobiographical reasoning), cognitive variables (negative explanatory style, cognitive reappraisal strategies, and rumination), and psychopathology (symptoms of depression and anxiety). Narratives of life story high, low, and turning points were collected from 164 young adults. Findings for negative self-event connections are reported here. Young adults who made some, as opposed to no, negative self-event connections reported greater symptoms of depression and anxiety and were more likely to report higher levels of ruminative thinking and less likely to use adaptive cognitive reappraisal strategies. Whether participants drew negative self-event connections predicted depression over and above the variance explained by negative explanatory style and cognitive reappraisal strategies and interacted with explanatory style to predict depression. In contrast, negative self-event connections did not incrementally predict anxiety over and above the cognitive variables. Results are discussed in terms of our current understanding of the factors that predict psychological distress.